New genotype-phenotype correlations in a large European cohort of patients with sarcoglycanopathy - Alonso-Pérez, Jorge; González-Quereda, Lidia; Bello, Luca; Guglieri, Michela; Straub, Volker; Gallano, Pia; Semplicini, Claudio; Pegoraro, Elena; Zangaro, Vittoria; Nascimento, Andrés; Ortez, Carlos; Comi, Giacomo Pietro; et al. (Brain, 2020)
Sarcoglycanopathies comprise four subtypes of autosomal recessive limb-girdle muscular dystrophies (LGMDR3, LGMDR4, LGMDR5 and LGMDR6) that are caused, respectively, by mutations in the SGCA, SGCB, SGCG and SGCD genes. In 2016, several clinicians involved in the diagnosis, management and care of patients with LGMDR3-6 created a European Sarcoglycanopathy Consortium. The aim of the present study was to determine the clinical and genetic spectrum of a large cohort of patients with sarcoglycanopathy in Europe. This was an observational retrospective study. A total of 33 neuromuscular centres from 13 different European countries collected data of the genetically confirmed patients with sarcoglycanopathy followed-up at their centres. Demographic, genetic and clinical data were collected for this study. Data from 439 patients from 13 different countries were collected. Forty-three patients were not included in the analysis because of insufficient clinical information available. A total of 159 patients had a confirmed diagnosis of LGMDR3, 73 of LGMDR4, 157 of LGMDR5 and seven of LGMDR6. Patients with LGMDR3 had a later onset and slower progression of the disease. Cardiac involvement was most frequent in LGMDR4. Sixty per cent of LGMDR3 patients carried one of the following mutations, either in a homozygous or heterozygous state: c.229C>T, c.739G>A or c.850C>T. Similarly, the most common mutations in LMGDR5 patients were c.525delT or c.848G>A. In LGMDR4 patients the most frequent mutation was c.341C>T. We identified onset of symptoms before 10 years of age and residual protein expression lower than 30% as independent risk factors for losing ambulation before 18 years of age, in LGMDR3, LGMDR4 and LGMDR5 patients. This study reports clinical, genetic and protein data of a large European cohort of patients with sarcoglycanopathy. Improving our knowledge about these extremely rare autosomal recessive forms of LGMD was helped by a collaborative effort of neuromuscular centres across Europe. Our study provides important data on the genotype-phenotype correlation that is relevant for the design of natural history studies and upcoming interventional trials in sarcoglycanopathies.
Keywords: dospělí; sarkoglykanopatie; Female; Europe; dítě; předškolní dítě; Adult; mladý dospělý; ženské pohlaví; pletencové svalové dystrofie; Muscular Dystrophies, Limb-Girdle; Adolescent; lidé; Evropa; Sarcoglycanopathies; kohortové studie; Cohort Studies; retrospektivní studie; genetické asociační studie; Male; Aged; Child, Preschool; Young Adult; lidé středního věku; Child; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; mladiství; Genetic Association Studies; Humans